Controversial nuclear ban treaty - Robert Margulies (Intereconomics, 1967)
The non-proliferation of atomic weapons in the hopes of achieving worldwide disarmament is the general aim of the nuclear ban treaty; this has the support of many nations. However, discussion about the projected agreement has recently moved further and further away from the military sphere and towards the possible economic effects of the planned treaty structure. The anxieties and reservations expressed by many countries—in particular European countries—are directed mainly against control over the peaceful use of atomic energy in countries without nuclear weapons. The agreement to ban atomic weapons entails a large number of purely economic considerations. Foremost is anxiety about the unrestricted progress of research and development in the sphere of peaceful uses of nuclear technology in those industrial countries which are really very little concerned with the real purpose of the nuclear ban treaty. The following interview may bring us one step nearer to an understanding of the economic aspects of the nuclear ban treaty, the full extent of whose consequences to research and industry cannot yet be foretold.
Keywords: 330; Interview